Crohn's disease or TB – the perennial question and diagnostic pitfalls. (3rd April 2012) - Maitra, Rudra Krishna; Bowling, Tim; Venkatesan, Pradhib; Maxwell-Armstrong, Charles
Abstract : A previously healthy 28-year old lady from Saudi Arabia presented with recurrent peri-anal abscesses progressing to fistula-in-ano. These were treated with incision and drainages and with setonisation of the fistula. Multiple biopsy and culture specimens were taken to rule out tuberculosis (TB) or Crohn's disease – all showed granulomatous disease suggestive of either Crohn's or TB, no mycobacteria were grown. MRI scanning also suggested either TB or Crohn's disease. Tuberculin skin test was inconclusive and Quantiferon Gold test was negative. Treatment for Crohn's was started with oral prednisolone – the patient deteriorated and adalimumab (tumour necrosis factor α antagonist) was commenced. With continued deterioration in the absence of intra-abdominal abscesses, a clinical diagnosis of TB was made, Crohn's treatment suspended and quadruple therapy for TB was initiated. The patient rapidly improved and a delayed re-look histological specimen identified an isolated mycobacterium. Subsequent cultures confirmed drug-sensitive TB. The lady is currently well on TB eradication regimen.